PEMIJAHAN IKAN BETOK (Anabas testudineus) SEMI ALAMI DENGAN SEX RATIO BERBEDA - Burmansyah .; Muslim .; Mirna Fitrani (Jurnal Akuakultur Rawa Indonesia, 2013)
ABSTRACT The aim  of the research was to fiad out sex ratio proportion on ovulation time, fecundity, fertilization, and hatching percentage of climbing perch eggs. The research used Completely Randomized Design with four treatments and three replicates with P as treatment code. The treatment used was ratio between female and male including P1(1:1), P2(1:2), P3(1:3), and P4(1:4). Observed parameters were ovulation time, fecundity, fertilization, hatching percentage, and water quality. Observed parameters were ovulation time, fecundity, fertilization, hatching percentage, and water quality. The Results showed that all treatment did not affected significantly affentedthe observed parameter (P<0,05). P2 treatment provided the fastest ovulation time with 137.33 minute, highest fecundity value provided by P4 with 18.533 eggs grains. Eggs fertilization rates of eggs on each treatmentwas 100%, and the highest hatching percentage was given by P1 treatment withnumber 91.57%. Ranges of water quality parameters recorded on  research                      were temperature 28-29 0C, pH 6.2-6.5, disollved oxygen 6.11-6.79 ppm and                       amonia 0.010-0.038 ppm. Keywords : Honey, masculinitation, dipping time, male percentage